Temporal variability in large grazer space use in an experimental landscape - Raynor, E. J.; Joern, Anthony; Skibbe, A.; Sowers, M.; Briggs, John M.; Laws, A. N.; Goodin, Douglas G. (My University, 2017)
Land use, climate change, and their interaction each have great potential to affect grazing systems. With anticipated more frequent and extensive future drought, a more complete understanding of the mechanisms that determine large grazer landscape-level distribution under varying climatic conditions is integral to ecosystem management. Using an experimental setting with contrasting fire treatments, we describe the inter-annual variability of the effect of landscape topography and disturbance from prescribed spring fire on large grazer space use in years of variable resource availability. Using GPS telemetry, we investigated space use of plains bison (Bison bison bison) as they moved among watersheds managed with variable experimental burn treatments (1-, 2-, 4-, and 20-year burn intervals) during a seven-year period spanning years of average-to-above average forage production and severe drought. At the landscape scale, bison more strongly favored high-elevation and recently burned watersheds with watersheds burned for the first time in 2 or 4 yr consistently showing higher use relative to annually burned watersheds. In particular, watersheds burned for the first time in 4 yr were avoided to lesser extent than other more frequently burned watersheds during the dormant season. This management type also maintained coupling between bison space use and post-fire regrowth across post-drought growing season months, whereas watersheds with more frequent fire-return intervals attracted bison in only the first month post-fire. Hence, fire frequency played a role in maintaining the coupling of grazer and post-fire regrowth, the fire-grazer interaction, in response to drought-induced reduction in fuel loads. Moreover, bison avoided upland habitat in poor forage production years, when forage regrowth is less likely to occur in upland than in lowland habitats. Such quantified responses of bison to landscape features can aid future conservation management efforts and planning to sustain fire-grazer interactions and resulting spatial heterogeneity in grassland ecosystems.
Citation: Raynor, E. J., Joern, A., Skibbe, A., Sowers, M., Briggs, J. M., Laws, A. N., & Goodin, D. (2017). Temporal variability in large grazer space use in an experimental landscape. Ecosphere, 8(1), 18. doi:10.1002/ecs2.1674
Keywords: Behavioral Shifts; Climatic Variability; Drought; Fire Frequency; Grazing Systems; Konza Prairie Biological Station